Fiscal policy transmission in a non-Ricardian model of a monetary union - Christoph Bierbrauer (Osnabrück University, Institute of Empirical Economic Research, 2017)
We present an analytically tractable two-country New Open Economy Macroeconomics model of a currency union featuring an overlapping gen- erations structure of the Blanchard (1985)-Yaari (1965) type. It enables us to study the transmission and spillover effects of a wider range of fiscal shocks in comparison to the standard model. We show that, depending on the financing decision of the government, fiscal policy measures can have very different effects on key macroeconomic vari- ables such as consumption and output. Moreover, the spillovers of national fiscal policy depend on the composition of government spending, the type of the fiscal measure and the cross-country substitutability between goods.
Keywords: E62; F33; F41; H31; H50; H63; 330; Overlapping generations; New open economy macroeconomics; Public Debt; Decentralized fiscal policy; Monetary union